A proof of the Product Rule appears below. Provide a justification for each step. a. d d x [ f ( x ) ⋅ g ( x ) ] = lim h → 0 f ( x + h ) g ( x + h ) − f ( x ) g ( x ) h Definition of derivative b. = lim h → 0 f ( x + h ) g ( x + h ) − f ( x + h ) g ( x ) + f ( x + h ) g ( x ) − f ( x ) g ( x ) h Adding and subtracting the same quantify is the same as adding 0. c. = lim h → 0 f ( x + h ) g ( x + h ) − f ( x + h ) g ( x ) h + lim h → 0 f ( x + h ) g ( x ) − f ( x ) g ( x ) h The limit of a sum is the sum of the limits. d. = lim h → 0 [ f ( x + h ) ⋅ g ( x + h ) − g ( x ) h ] + lim x → 0 [ g ( x ) ⋅ f ( x + h ) − f ( x ) h ] e. = f ( x ) ⋅ lim h → 0 g ( x + h ) − g ( x ) h + g ( x ) ⋅ lim h → 0 f ( x + h ) − f ( x ) h The limit of a product is the product of the limit and lim h → 0 f ( x + h ) = f ( x ) . f. f ( x ) ⋅ g ' ( x ) + g ( x ) ⋅ f ' ( x ) Definition of derivative g. f ( x ) ⋅ [ d d x g ( x ) ] + g ( x ) ⋅ [ d d x f ( x ) ] Using Leibniz notation
A proof of the Product Rule appears below. Provide a justification for each step. a. d d x [ f ( x ) ⋅ g ( x ) ] = lim h → 0 f ( x + h ) g ( x + h ) − f ( x ) g ( x ) h Definition of derivative b. = lim h → 0 f ( x + h ) g ( x + h ) − f ( x + h ) g ( x ) + f ( x + h ) g ( x ) − f ( x ) g ( x ) h Adding and subtracting the same quantify is the same as adding 0. c. = lim h → 0 f ( x + h ) g ( x + h ) − f ( x + h ) g ( x ) h + lim h → 0 f ( x + h ) g ( x ) − f ( x ) g ( x ) h The limit of a sum is the sum of the limits. d. = lim h → 0 [ f ( x + h ) ⋅ g ( x + h ) − g ( x ) h ] + lim x → 0 [ g ( x ) ⋅ f ( x + h ) − f ( x ) h ] e. = f ( x ) ⋅ lim h → 0 g ( x + h ) − g ( x ) h + g ( x ) ⋅ lim h → 0 f ( x + h ) − f ( x ) h The limit of a product is the product of the limit and lim h → 0 f ( x + h ) = f ( x ) . f. f ( x ) ⋅ g ' ( x ) + g ( x ) ⋅ f ' ( x ) Definition of derivative g. f ( x ) ⋅ [ d d x g ( x ) ] + g ( x ) ⋅ [ d d x f ( x ) ] Using Leibniz notation
Solution Summary: The author explains how the value of different functions is used to define the derivatives of the function.
2. We want to find the inverse of f(x) = (x+3)²
a. On the graph at right, sketch f(x).
(Hint: use what you know about
transformations!) (2 points)
b. What domain should we choose to
get only the part of f (x) that is one-
to-one and non-decreasing? Give
your answer in inequality notation. (2
points)
-
c. Now use algebra to find f¯¹ (x). (2
points)
-4-
3-
2
1
-4
-3
-2
-1
0
1
-1-
-2-
--3-
-4
-N-
2
3
4
1. Suppose f(x) =
2
4
==
x+3
and g(x) = ½-½. Find and fully simplify ƒ(g(x)). Be sure to show all
x
your work, write neatly so your work is easy to follow, and connect your expressions
with equals signs. (4 points)
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, calculus and related others by exploring similar questions and additional content below.